2012
DOI: 10.2475/07.2012.03
|View full text |Cite
|
Sign up to set email alerts
|

Paleogeographic and tectonic evolution of the Pranhita-Godavari Valley, Central India: a Stratigraphic perspective

Abstract: The Pranhita-Godavari Valley of central India preserves records of repeated opening and closing of Proterozoic and Gondwana rifts along the zone of NW-SE trending Neoarchean suture between the Dharwar and Bastar cratonic nuclei. The Proterozoic succession in the Valley comprises several major unconformity-bound sequences, each with a distinctive set of litho-assemblage, deposited under diverse tectonic environments with highly variable modes and tempos of sedimentation. Analysis of sedimentary attributes of un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 96 publications
1
29
0
Order By: Relevance
“…1). Although previous workers had suggested that the Proterozoic sedimentary rocks in the basin were likely to be the preserved relics of a much larger basin (Ramakrishnan and Vaidyanathan, 2008), sedimentological studies by Chaudhuri et al (2012) demonstrated that the rocks were deposited largely within the present rift boundaries. The rift developed along the NWeSE trending Karimnagar Orogenic Belt, which delineates a Neoarchaean granulite belt between the Dharwar and Bastar cratonic nuclei.…”
Section: Geological Settingmentioning
confidence: 94%
See 3 more Smart Citations
“…1). Although previous workers had suggested that the Proterozoic sedimentary rocks in the basin were likely to be the preserved relics of a much larger basin (Ramakrishnan and Vaidyanathan, 2008), sedimentological studies by Chaudhuri et al (2012) demonstrated that the rocks were deposited largely within the present rift boundaries. The rift developed along the NWeSE trending Karimnagar Orogenic Belt, which delineates a Neoarchaean granulite belt between the Dharwar and Bastar cratonic nuclei.…”
Section: Geological Settingmentioning
confidence: 94%
“…2). Both Pur ana and Gondwana outcrop belts maintain similar depositional and structural trends (Chaudhuri et al, 2012), and Pur ana formations can be lithostratigraphically correlated across the valley into several unconformity-bound sequences (Chaudhuri, 2003;Chaudhuri et al, 2012). The sequences, by turn, can be classified into at least three 1st or 2nd order depositional cycles (Fig.…”
Section: Geological Settingmentioning
confidence: 97%
See 2 more Smart Citations
“…Sustained field mapping together with facies analysis over the last few decades by many workers has confirmed that King's three-fold classification was not adequate from the point of view of basin evolution (Nageswara Rao 1964;Basumallick 1967;Chaudhuri 1970Chaudhuri , 1985Chaudhuri , 2003Subba Raju et al 1978;Srinivasa Rao et al 1979a, b;Sreenivasa Rao 1985, 2001Chaudhuri et al 2012). In fact, because of episodic uplift, differential erosion and the consequent development of several tectonically mediated unconformities (Chaudhuri et al 2012), dramatic facies variations across the basin, post-Purana development of the Gondwana rift system and fragmentation of Purana outcrops, correlation of different outcrops across the valley and classification of the said successions in relation to the Proterozoic evolutionary events in the PG Valley remain difficult. As a result, a number of contradictions remain among the schemes of classification currently in vogue, and all hinge primarily on the consideration of the unconformity-bound successions as lithostratigraphic units of 'Subgroup', 'Group' and 'Supergroup' ranks (Tables 12.1 & 12.2).…”
mentioning
confidence: 99%